2x+11=-33-x

Simple and best practice solution for 2x+11=-33-x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+11=-33-x equation:


Simplifying
2x + 11 = -33 + -1x

Reorder the terms:
11 + 2x = -33 + -1x

Solving
11 + 2x = -33 + -1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'x' to each side of the equation.
11 + 2x + x = -33 + -1x + x

Combine like terms: 2x + x = 3x
11 + 3x = -33 + -1x + x

Combine like terms: -1x + x = 0
11 + 3x = -33 + 0
11 + 3x = -33

Add '-11' to each side of the equation.
11 + -11 + 3x = -33 + -11

Combine like terms: 11 + -11 = 0
0 + 3x = -33 + -11
3x = -33 + -11

Combine like terms: -33 + -11 = -44
3x = -44

Divide each side by '3'.
x = -14.66666667

Simplifying
x = -14.66666667

See similar equations:

| [n-1]*4=28 | | x^2+-2x+2=0 | | 4n+2n=21+7 | | 8a+1=25 | | x^2-12x+8y+20=0 | | ln(y)=x-ln(C) | | 12x-220=2x-10 | | 89-6x=21x+17 | | 5+x=-20 | | -2x-(-8)=-8 | | 0-13-8x=x+19 | | 2(a+1)+a+3= | | 12=72 | | F=w+7m | | 4x+1=7(x+3) | | 43-5x=13x-17 | | 184(x+4)=24 | | 55-5x=9x+16 | | 5x-2y+38=0 | | 12x-30=60 | | 2lg(x+1)=4 | | 76-5x=7x+19 | | 11m-6=7m | | y=(-4)-14 | | 2x-4=8x-53 | | 3*103x=3000 | | 2x+38=16x-72 | | -3(-3)-3y=3 | | 12x-7=9x+1 | | 2x+3y-20=0 | | 2a-(8a+1)-(a+2).5=9 | | -129-9x=7x+16 |

Equations solver categories